2021
DOI: 10.3390/nu13103443
|View full text |Cite
|
Sign up to set email alerts
|

Is the Phenylalanine-Restricted Diet a Risk Factor for Overweight or Obesity in Patients with Phenylketonuria (PKU)? A Systematic Review and Meta-Analysis

Abstract: Although there is a general assumption that a phenylalanine (Phe)-restricted diet promotes overweight in patients with phenylketonuria (PKU), it is unclear if this presumption is supported by scientific evidence. This systematic review aimed to determine if patients with PKU are at a higher risk of overweight compared to healthy individuals. A literature search was carried out on PubMed, Cochrane Library, and Embase databases. Risk of bias of individual studies was assessed using the Quality Assessment Tool fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Understanding the upper phenylalanine content of fruits and vegetables that can be tolerated without measurement in patients with PKU on dietary treatment only is particularly important. In PKU, the rate of obesity although similar to the general population is high [ 18 ], but fruit and vegetable intake is low [ 19 ]. It is well established that vegetables are good sources of bioactive compounds, including dietary fiber, micronutrients and phytochemicals, and they are associated with a reduced risk of chronic disease; strategies to increase the intake and variety of low-energy-dense vegetables are essential [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the upper phenylalanine content of fruits and vegetables that can be tolerated without measurement in patients with PKU on dietary treatment only is particularly important. In PKU, the rate of obesity although similar to the general population is high [ 18 ], but fruit and vegetable intake is low [ 19 ]. It is well established that vegetables are good sources of bioactive compounds, including dietary fiber, micronutrients and phytochemicals, and they are associated with a reduced risk of chronic disease; strategies to increase the intake and variety of low-energy-dense vegetables are essential [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several studies have found the female PKU population (both adults and children) to have increased levels of overweight and obesity in comparison to the general population [ 25 , 30 , 31 ]. In a recent systematic review, Rodrigues et al [ 32 ] conducted a meta-analysis and found that the BMI of patients with PKU was similar to their healthy controls; however, a subgroup of patients with classical PKU had a significantly higher BMI. The meta-analysis dataset included both adults and children; the age range was between 0.2 and 52 years.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity : The prevalence of overweight and obesity in all women of childbearing age is high, and approximately 39% of the world’s adult population is overweight, with 13% being obese [ 25 ]. Although a recent systematic review and meta-analysis of women with PKU [ 26 ] found that the body mass index (BMI) of patients with PKU was similar to their healthy controls, a subgroup of patients with classical PKU had a significantly higher BMI. The authors also noted a trend towards a higher BMI in females with PKU in all studies with male and female datasets.…”
Section: Nutritional Vulnerability Of Women With Pku In Their Reprodu...mentioning
confidence: 99%